Comparison between Topical Olopatadine Hydrochloride 0.1% and Ketotifen Fumarate 0.025% for the Relief of Symptoms of Vernal Keratoconjunctivitis (VKC) - Tariq Mahmood Arain,Zaheer Uddin A. Qazi, Muhammad Rizwan Khan, Muhammad Naeem Azhar, Muhammad Sufyan Aneeq Ansari (Pakistan Journal of Ophthalmology, 2018)
Purpose: To compare the topical administration of Olopatadine HCL 0.1 % and Ketotifen fumarate 0.025% for the relief of symptoms of VKC. Material and Methods: From April 2010 to September 2010, this randomized controlled trial was conducted on 120 diagnosed patients of VKC from out-door patient department of Bahawal Victoria Hospital Bahawalpur, equally and randomly enrolled in two groups. In group A patients were given topical Olopatadine HCL 0.1% QID and in group B topical Ketotifen fumarate 0.025% QID. Regular follow up of all the patients were done for relief of symptoms on day 0, 7 and 28. Final outcome was determined at the end of 4th week from start of the treatment. Results: All 120 patients completed the study with regular follow up. Patients presented with multiple symptoms and clinical types of VKC. All the patients felt early and significant relief in their symptoms, but the effectiveness and tolerability of Olopatadine HCL 0.1% was significantly more (P<0.05) as compared to ketotifen fumarate 0.025%. Conclusion: Both topical Olopatadine HCL 0.1% and ketotifen fumarate 0.025% are effective in treating the VKC. However, Olopatadine HCL 0.1% provides greater symptomatic relief in patients of VKC as compared to Ketotifen fumarate 0.025%.